Mawqif Ibn Mālik ʿan al-khilāf bayna al-baṣriyyīn wa al-kūfiyyīn fī Kitāb Alfiyyat Ibn Mālik - Munir, Dede Rizal (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
SCIENCE NAHWU is one of the basic parts of grammar in Arabic to find out the position of the word in a sentence and the form of the last letter or vowel of a word. As we know, one of the books that discusses nahwu is the book of al-fiyah ibn malik. Al-fiyyah is a nadhom book of Arabic rules that has a Rajaz rhythm and summarizes the discussion by covering a deep meaning. Thus the purpose of this study is to find out the nadzhom that there are differences of opinion between the kuffah and bashrah scholars, to find out the problems of differences of opinion in the discussion of al-fiyyah. The research method uses two sources, namely primary and applied sources. The main source in this study is the thought of Nahwu ibn Malik in the book of al-Fiyyah. While the applied sources are related to the explanation of al-fiyyah such as the explanation of ibn aqil, al-makudi, ibn hamdun, al-khudhori and books related to the science of nahwu. Research results After conducting research on ibn malik's attitude between bashrah and kuffah scholars in the al-fiyyah book, some of which include differences of opinion between the bashrah and kuffah scholars in the al-fiyyah book contained in 20 chapters.